Rawums — “Wild Young People” in Literature. Pop-authors of the 1980s - Enno Stahl (Studia Litterarum)
The term popliterature emerged in the middle of the 1990s. Although there is no satisfactory definition of the term’s exact meaning, it has proven to be very successful as a code for marketing activities. The publishing house Kiepenheuer & Witsch played important role in the first successful wave of popliterature in the 1990s. It is less known that the publisher promoted a similar popliterary attack already in the 1980s, which failed perhaps because the flashing promotion badge, the “p-word” was absent. The starting point was a book Der große Hirnriss by Peter Glaser and Niklas Stiller published by the Rowohlt publishing house. It was followed by Rainald Goetz intervention in the ceremony of a famous Bachmann-prize when he gained publicity by cutting himself a forehead. Shortly after, there appeared his first novel Irre. The groundbreaking anthology “Rawums!” edited by Peter Glaser and published again by Kiepenheuer & Witsch, brought together authors many of whom formed a circle around a music magazine SPEX. They intended to create new “wild” literature analogous to the paintings of “Jungen Wilden” who were gaining popularity in those days. The last achievement of the brief blossom of popliterature in the 1980s was Joachim Lottmann book Mai, Juni, Juli (May, June, July) which was something like the “missing link” between popliterature of the 1980s and 1990s.